PENINGKATAN MINAT BERWIRAUSAHA BAGI SISWA SMKN I KALIANGET DENGAN PELATIHAN DAN PENDAMPINGAN SHOPEE AFFILIATE PROGRAM - Ratna, Purwati; Rahman, Sindi Arista; Hopid, Hopid; Santoso, Ribut (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2024)
Entrepreneurship training and mentorship have become essential needs for vocational high school students to compete in the digital economy era. The Shopee Affiliate Program offers an opportunity for young people to venture into online business with minimal capital and low risk. This community service activity aims to increase the entrepreneurial interest of students at SMKN I Kalianget through a series of technical training and mentoring in using the Shopee Affiliate Program. The methods used in this activity include a participatory approach with stages of socialization, practical training, and evaluation. The results of the activity showed a significant increase in students' interest and knowledge regarding digital entrepreneurship opportunities. The evaluation was conducted through questionnaires and interviews, indicating that the majority of students were interested in utilizing Shopee Affiliate as an initial step in entrepreneurship.